Nickel catalysed hydrogenation of aldol condensation product of furfural with cyclopentanone to C15 cyclic ethers. Issue 2 (February 2016) - Hronec, Milan; Fulajtárová, Katarína; Liptaj, Tibor; Soták, Tomáš; Prónayová, Naďa
Abstract: This work describes a simple method for selective hydrogenation of 2, 5‐bis(2‐furylmethylidene)cyclopentan‐1‐one (F2 C) to C15 cyclic ethers. F2 C is the product of base catalysed aldol condensation of furfural with cyclopentanone. The cyclic ethers can be used as potential additives for transportation fuels. Raney nickel and supported nickel catalysts have shown very high activity and selectivity for F2 C hydrogenation at mild reaction temperatures (70‐110 °C) and hydrogen pressures 0.1‐0.2 MPa. Hydrogenation was studied in THF, dioxane, acetic acid and n‐octane as the solvents. In n‐octane which dissolves formed cyclic ethers the rates of hydrogenation are very high; throughout 55 min of F2 C hydrogenation at a temperature of 80 °C and 0.2 MPa of hydrogen, the C15 mono‐ and bis‐cyclic ethers are produced in more than 19 and 67 mol % yields, respectively. Abstract : A simple method for nickel catalysed hydrogenation of 2, 5‐bis(2‐furylmethylidene)cyclopentan‐1‐one (F2 C) to C15 cyclic ethers is described. The F2 C is condensation product of furfural with cyclopentanone and the products can be used potentially as additives for transportation fuels. Raney nickel catalysts have shown very high activity and selectivity at mild reaction temperatures and hydrogen pressures.